CHARACTERISTICS OF SELECTED SUMATERAN TERTIARY COALS REGARDING THEIR PETRO- GRAPHIC ANALYSES - BUKIN DAULAY; BINARKO SANTOSO (Puslitbang tekMIRA, 2008)
Type and rank variation of selected Sumateran (Ombilin and Bukit Asam) Tertiary coals were as- sessed by petrographic examination of 170 samples. The coals are dominated by vitrinite, common liptinite and rare inertinite and mineral matter. Vitrinite macerals are dominated by detrovitrinite and telovitrinite. Resinite, cutinite and suberinite are the dominant liptinite macerals in the coals. Inertinite macerals in the coals consist of semifusinite, sclerotinite and inertodetrinite. The higher vitrinite re- flectance of some coals is a result of the local and variable effects of igneous intrusions in both areas. Similarities in the type and rank characteristics in the coals reflect their geological setting, climatic influence and peat conditions.